Acoustic insulation performance of a honeycomb panel using a transfer matrix method. (November 2018) - Jung, Jae-Deok; Hong, Suk-Yoon; Song, Jee-Hun; Kwon, Hyun-Wung
Honeycomb panels have good mechanical properties and are widely used in various industries because of their high strength-to-weight ratio. However, more research into their acoustic insulation is needed. In this study, a transfer matrix was derived for the acoustic insulation performance prediction of a honeycomb panel. To properly derive the transfer matrix for the model, it should be configured from the relationship between the pressure and particle velocity of the front and rear sections of the honeycomb panel. Each type (fluid, solid, etc.) consisting of a layer was analyzed by a continuous pressure and velocity condition. The numerical results were verified through experimental results using the intensity method. We confirmed that the two results (numerical and experimental result) were in good agreement within approximately 2 dB. Finally, the acoustic insulation performance was studied in relation to the honeycomb thickness, cell size, cell-wall thickness, and cell shape. We observed that smaller cell sizes and thicker cell walls improved the insulation performance. We confirmed that acoustic insulation performance of honeycomb panels can be improved by changing the cell design.